2007
DOI: 10.1080/00909880701611060
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami Warning Dissemination in Mauritius

Abstract: Post-disaster communication surveys are important in order to improve future disaster warning efficiency. Mauritius, a small island nation in the western Indian Ocean, was in the path of the tsunami of December 2004 but experienced only minimal wave impact. This is fortunate because the results of this survey show very slow warning dissemination through the population. Television and radio were equally effective in disseminating the initial warning information, but television far exceeded radio's reach as rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…The data supports this assumption, even in an environment with scarce Internet access. For those with higher levels of education it is possible Internet sources fulfilled the complementary "interpersonal networking" functions described by Perry (2007). However, given the limited access to the Internet before and after the earthquake, it is not clear whether the Internet had sufficiently diffused through Haitian society so as to provide a complementary function for those who used the technology, or if the Internet simply served to reinforce information acquired through sources like newspapers.…”
Section: Repertoire Complementarity or Convergence?mentioning
confidence: 95%
See 3 more Smart Citations
“…The data supports this assumption, even in an environment with scarce Internet access. For those with higher levels of education it is possible Internet sources fulfilled the complementary "interpersonal networking" functions described by Perry (2007). However, given the limited access to the Internet before and after the earthquake, it is not clear whether the Internet had sufficiently diffused through Haitian society so as to provide a complementary function for those who used the technology, or if the Internet simply served to reinforce information acquired through sources like newspapers.…”
Section: Repertoire Complementarity or Convergence?mentioning
confidence: 95%
“…The information needs of earthquake survivors are thus likely to be multifaceted, and the communication of information through media to meet those needs is a crucial part of responding to earthquakes. Indeed, literature has demonstrated the critical role media play in the aftermath of disasters (e.g., Littlefield & Quenette, 2007;Perry, 2007;Procopio & Procopio, 2007). So-called old and new technologies may play a role in meeting challenges created by disasters (Gunawardene & Noronha, 2007).…”
Section: Disasters Information Seeking and Mediamentioning
confidence: 98%
See 2 more Smart Citations
“…A study that evaluated the dissemination of tsunami warnings in Mauritius (Perry, 2007) found that both television and radio were equally effective in disseminating the initial tsunami warning and that television became more important later. The impact of an interpersonal warning system was minimal, though, and media messages did not provide sufficient and accurate enough information about the disaster.…”
Section: Resultsmentioning
confidence: 99%